Configurable 3D rowing model renders realistic forces on a simulator for indoor training - Basalp, E.; Bachmann, P.; Gerig, N.; Rauter, G.; Wolf, P. (Applied Sciences, 2020)
In rowing, rowers need outdoor and indoor training to develop a proficient technique. Although numerous indoor rowing machines have been proposed, none of the devices can realistically render the haptic, visual, and auditory characteristics of an actual rowing scenario. In our laboratory, we developed a simulator to support rowing training indoors. However, rendered forces with the initial rowing model, which was based on a simplified fluid dynamic model that approximated the drag/lift forces, were not perceived realistic enough for indoor training by expert rowers. Therefore, we implemented a new model for the blade-water interaction forces, which incorporates the three-dimensional rotation of the oar and continuously adjusts drag/lift coefficients. Ten expert rowers were asked to evaluate both models for various rowing aspects. In addition, the effect of individualization of model parameters on the perceived realism of rowing forces was elaborated. Based on the answers of the experts, we concluded that the new model rendered realistically resistive forces and ensured a smooth transition of forces within a rowing cycle. Additionally, we found that individualization of parameters significantly improved the perceived realism of the simulator. Equipped with a configurable rowing model, our simulator provides a realistic indoor training platform for rowers.